PENGARUH MANAJEMEN LABA, TAX AVOIDANCE, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Ika Amanda Lubis; Anggiat Situngkir (Jurnal Akuntansi dan Bisnis, 2026)
This study aims to examine the effect of earnings management, tax avoidance, and leverage on firm value. This research is quantitative research. The data used in this study are secondary data in the form of financial reports of non-cyclical consumer sector companies obtained from the Indonesia Stock Exchange (IDX) and the company's official website. The sampling method in this study was purposive sampling, so that 38 samples were obtained from 130 companies that became the study population. The test was conducted using multiple linear regression analysis with SPSS Version 27. The results showed that the earnings management variable had no effect on firm value, while the tax avoidance and leverage variables had an effect on firm value.